The Effect Of Parking Management Information System On Performance With Job Satisfaction as A Mediation Variable (Study on Public Roadside Parking Attendants in Pekalongan City) - Hari Putra Setiawan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Roadside parking management plays a strategic role in supporting public services and increasing Regional Original Income (PAD). This study aims to analyze the effect of the Parking Management Information System and competence on parking attendant performance, with job satisfaction as a mediating variable. The research method uses a quantitative approach with a survey of 108 parking attendants in Pekalongan City. Data were analyzed using linear regression and mediation tests. The results of the study show that (1) the Parking Management Information System has a positive and significant effect on the performance of public roadside parking attendants in Pekalongan City, (2) Competence has a positive and significant effect on the performance of public roadside parking attendants in Pekalongan City, (3) the Parking Management Information System has a positive and significant effect on the job satisfaction of public roadside parking attendants in Pekalongan City, (4) Competence does not have a positive and significant effect on the job satisfaction of public roadside parking attendants in Pekalongan City, (5) Job satisfaction has a positive and significant effect on the performance of public roadside parking attendants in Pekalongan City, (6) Job satisfaction is able to partially mediate the effect of the Parking Management Information System on the performance of parking attendants, and (7) Job satisfaction is able to partially mediate the effect of Competence on the performance of parking attendants.